ANALISIS SISTEM PENCATATAN PIUTANG SPAREPART PADA PT. SINAR GALESONG PRIMA - Sondakh, Patrick Richard; Karamoy, Herman; Afandi, Dhullo (Universitas Sam Ratulangi, 2017)
As the times progressed, development in every country was very rapid. This is seen from the level of development of science and technology, social, and politics. All the countries of the world are competing to use all the skills and knowledge they have to adapt to these developments. Similarly, in order to support the national development program, then various government agencies and private participated in various efforts to support the success of nation building. So with the better the nation's development, Indonesia's economy is also improving. The object of this research is PT. Sinar Galesong Prima is a trading company that sells Suzuki car unit, sells original Suzuki sparepart, serves maintenance service and body repair for car. In the sale of spare parts in Sinar Galesong Prima there are two kinds of sales, namely sales in cash and on credit. The purpose of this study is to analyze whether or not the system of recording receivables spare parts at PT. Sinar Galesong Prima. The method used is the descriptive method, by identifying the data used in connection with the spare parts to be sold, identifying the system of recording and reporting of sales transactions, evaluating the advantages / disadvantages of applying the accounting system for transactions and reporting transactions, and drawing conclusions. The research results can be in the know that In the process of accounting, PT. Sinar Galesong Prima refers to the generally accepted Accounting Standards and PSAK and has created Accounting SOP in the form of Financial Accounting Guidelines (PAK) applied in the company. PT. Sinar Galesong Prima Manado uses the accrual basis (accrul basic) and records the non-deducted receivables using the allowance or reserve method. Based on the aspects of Recording, reporting and disclosure, the accounting system of PT. Sinar Galesong Prima receivables is in accordance with the applicable PSAKKeywords : Recording System Receivables